2020
DOI: 10.1088/1674-1056/ab7744
|View full text |Cite
|
Sign up to set email alerts
|

Two-step processed efficient perovskite solar cells via improving perovskite/PTAA interface using solvent engineering in PbI2 precursor*

Abstract: The morphology and interface of perovskite film are very important for the performance of perovskite solar cells (PSCs). The quality of perovskite film, fabricated via two-step spin-coating process, is significantly influenced by the morphology and crystallinity of PbI2 film. With the addition of additive dimethyl sulfoxide (DMSO) into the PbI2 precursor, the roughness and trap-state density of perovskite film have been significantly reduced, leading to the excellent contact between perovskite layer and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
1
7
1
Order By: Relevance
“…The PbI2 layer fabricated from only DMF solvent is low-crystalline. This result is inconsistent with the previous reports [19][20][21]. The boiling point of DMF, 153℃ is lower than that of DMSO, 189℃.…”
Section: Measurementscontrasting
confidence: 95%
See 2 more Smart Citations
“…The PbI2 layer fabricated from only DMF solvent is low-crystalline. This result is inconsistent with the previous reports [19][20][21]. The boiling point of DMF, 153℃ is lower than that of DMSO, 189℃.…”
Section: Measurementscontrasting
confidence: 95%
“…The device performance of the 0 vol% specimen is the best of five specimens. As reported in the previous papers [18][19][20][21], when the perovskite layer converted from the lowcrystalline PbI2 is used, the device performance is improved. We compared our fabrication process with the previous fabrication processes.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Several reports have demonstrated that there is high trap density at the interfaces of PSCs. Interfacial passivation is an effective way to enhance the performance of PSCs. However, due to the rougher surface of perovskite on the flexible substrate, the classic organic salt surface passivation strategy cannot seem to achieve desired results. Two-dimensional (2D) perovskite is an applicable interfacial passivation material, which has unexceptionable stability and water-tolerant properties. Assembling 2D perovskite onto 3D perovskite forming a 2D/3D perovskite heterojunction to improve the interfacial condition is an effective strategy to achieve high-performance and stable PSCs. More importantly, rough and loose surfaces of perovskite on the flexible substrate are beneficial for the reaction between residual PbI 2 and organic salt to form 2D perovskite.…”
Section: Interface Optimization For Enhancing Charge Extractionmentioning
confidence: 99%
“…[9][10][11] It is well known that post-thermal-annealing plays a key role in the formation of high-quality perovskite films, directly determining the photovoltaic performance of PSCs. [12][13][14][15] It mainly has three main objectives: (i) removing residual solvents after solution processing; (ii) promoting conversion from precursors to perovskite; (iii) increasing crystallinity and promoting the growth of perovskite crystal grains. [16][17][18][19][20] The post-annealing parameters, including temperature, duration and atmosphere, have critical effects on the crystallization, morphology of perovskite film and device performance.…”
mentioning
confidence: 99%